Perancangan Mesin Perajang Singkong - Romiyadi Romiyadi; Nopriadi Nopriadi (Jurnal Sains dan Ilmu Terapan, 2019)
Abstract— Cassava chopper machine is a tool for chopping cassava into thin sheets with a thickness of ± 1 to 2 mm. Not only that, this machine can also produce slices with the same thickness, cutting time is fast. This study aims to design a cassava chopper machine to produce cassava chips for the home industry scale. The design concept of this cassava chopper machine refers to the design concept of Darmawan (2012), namely with several stages, including requirements, project definition, project and preparation of product technical specifications, product concept planning, product design, to documents for product manufacture. The next process is analyzing needs, paying attention to planning considerations, and also paying attention to planning demands.